Combustion of agglomerated ultrafine aluminum powders in air; Combustion, Explosion, and Shock Waves; Vol. 38, № 6 - Ilyin A. P. Aleksandr Petrovich; Popenko E. M.; Gromov A. A. Aleksandr Aleksandrovich; Shamina Yu. Yu.; Tikhonov D. V. Dmitry Vladimirovich (2002, 2002)
Title screen